2005
DOI: 10.1038/sj.gt.3302677
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tolerance induction to immunodominant T-cell epitopes of Sendai virus on gene expression following repeat administration to lung

Abstract: Sendai virus (SeV) is able to transfect airway epithelial cells efficiently in vivo. However, as with other viral vectors, repeated administration leads to reduced gene expression. We have investigated the impact of inducing immunological tolerance to immunodominant T-cell epitopes on gene expression following repeated administration. Immunodominant CD4 and CD8 T-cell peptide epitopes of SeV were administered to C57BL/6 mice intranasally 10 days before the first virus administration with transmission-incompete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…20 We have previously shown that SeV administration evokes cellular and humoral immune responses in an animal model and that the level of neutralising antibodies (as measured by in vitro assays) increases after virus re-administration. 7 However, there was no correlation between neutralising antibody levels and residual gene expression (r 2 ¼0.046, P¼0.16). We have also shown that partial T-cell tolerance to SeV infection can be induced in mice after administration of immunodominant CD4 peptide eptiopes, but that a reduction in T-cells does not alter the levels of SeV-neutralising antibodies, or allow for repeat administration of the virus.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…20 We have previously shown that SeV administration evokes cellular and humoral immune responses in an animal model and that the level of neutralising antibodies (as measured by in vitro assays) increases after virus re-administration. 7 However, there was no correlation between neutralising antibody levels and residual gene expression (r 2 ¼0.046, P¼0.16). We have also shown that partial T-cell tolerance to SeV infection can be induced in mice after administration of immunodominant CD4 peptide eptiopes, but that a reduction in T-cells does not alter the levels of SeV-neutralising antibodies, or allow for repeat administration of the virus.…”
Section: Discussionmentioning
confidence: 97%
“…This is supported by our data. After a second dose of DF/SeV, expression is significantly reduced by 60 and 490% in mice 7 and sheep, respectively. However, because of the original extremely high gene transfer efficiency the residual gene expression after the second dose is still significantly higher than untransfected controls, or a single dose of non-viral vector.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3,4 Another study has demonstrated that a second successive dose of an SeV vector was able to transduce the murine airways, at B60% of the efficiency seen in naïve animals. 5 Although these earlier studies represented a significant advance in broadening the armamentarium of recombinant vectors suitable for transducing the murine airway, it was unclear whether vectors based on this murine virus would be capable of transducing larger animals. The latter would be seen as a necessary step toward clinical use, both to fulfill regulatory requirements and as a test of the ability of the vector system to work across various species, including humans, in vivo.…”
mentioning
confidence: 99%